Tonicum Activity of Red Ginger (Zingiber officinale var. Rubrum) and Elephant Ginger (Zingiber officinale var.Roscoe) Ethanol Extract in Vivo - Sitti Fauziah Noer; Ayu Wandira; Asri Mulya Ashari; Rita Kurnia Apindiati; Gusti Eva Tavita; Sri Zha Zha Dilla (Jurnal Biologi Tropis, 2023)
The increase in side effects due to the use of chemical drugs encourages people to return to nature, utilize the plants around them in dealing with health problems. Red ginger (Z. officinale Var Rubrum) and elephant ginger (Z. officinale var Roscoe) have been used empirically in medicine especially to boost immunity. This study aims to determine the tonic activity of the ethanol extract of red ginger and elephant ginger in vivo using the natatary exhaustin method with white rats (Rattus norvegicus) as test animals. The natural fatigue method was based on the resistance of the test animals to swimming in water after being treated with ethanol extract of red ginger and elephant ginger rhizome at a dose of 70 mg/kg body weight, using Na-CMC solution as a blank and caffeine solution as a positive comparison. Based on research data testing the tonic activity of red ginger and elephant ginger extracts in vivo showed that the tonic activity of red ginger ethanol extract with the swimming endurance of the test animals was for 27.72 seconds, longer than the swimming endurance of the treated animals. with elephant ginger ethanol extract which is only 16.46 seconds.